Research Agenda for Joint Management - Khanna, Pradeep (Indian Forester, 1994)
Joint Forest Management is being increasingy suggested as a solution to conservation problems of forests in India and developing countries. Philosophically the concept is ideal and needs to be supported without reservation. However, while implementing the programme in different Indian States, it has heen observed that the programme is unable to institutionalise due to number of problems. It is therefore, important to analyse the detail of programme and its viability in a shrinking resource base scenario. It is often seen that the JFM programme find. Success in support from non-forestry incentives. In this context, it is important to set up a clear research agenda to make the programme self sustainable and viable and to intitutionalise the same. The paper traces the history, analyses the bottlenecks and, in the process, attempts to set up research agenda for initiating a debate for arriving at a well based research programme to make JFM a success. The important research needs felt are to induce continuity of flow of benefits and enhance the level of benefits available to a level which could generate sustained enthusiasm and ensure viability of the programme on a long-term basis.